The Environmental Problems in the Context of Global Change: Possibilities and Limitations of Eco-Scientific Education from a Teaching Perspective - Aguilar-Correa, Cristián Manuel (Revista Electrónica Educare, 2023)
Objective. This essay aims to reflect on the limitations and possibilities of teaching eco-scientific education in the current planetary context of the environmental crisis. Discussion. This essay presents investigative findings on the subject, followed by epistemological and didactic analyses related to the environmental issue from the eco-scientific perspective. The paper recognizes the possibilities and limitations of teaching action. The essay then reflects on how eco-scientific knowledge, transdisciplinarity, and complementarity are gaining increasing importance and entering the educational and social sphere as new approaches to apprehending realities. Conclusion. There are epistemological and didactic obstacles that must be overcome to achieve the desired change, especially in topics related to eco-scientific issues. Considering the learning contexts is another great challenge; these facilitate the development of eco-citizen skills and attitudes loaded with localized knowledge and collective learning. Finally, in initial teacher training, there is reductionism in eco-scientific teaching, and it is necessary to create teaching and learning spaces that encourage reflection, questioning, debate, and the exchange of individual, local, and territorial knowledge.